Oil price shocks, policy uncertainty, and stock returns of oil and gas corporations. (February 2017) - Kang, Wensheng; Perez de Gracia, Fernando; Ratti, Ronald A.
Highlights: Oil demand-side shock has a positive effect on the return of oil and gas companies. Shocks to policy uncertainty have a negative effect on the return. Effects of oil shocks on the stock return are amplified by policy uncertainty. Return responses are heterogeneous among upstream, midstream, and downstream companies. Abstract: This paper investigates the effects of oil price shocks and economic policy uncertainty on the stock returns of oil and gas companies. We find that an oil demand-side shock has a positive effect on the return of oil and gas companies on average, whereas shocks to policy uncertainty have a negative effect on the return. Historical decomposition shows that the effects of oil shocks on the stock return are amplified by the endogenous policy uncertainty responses. These results are consistent with those for major integrated oil and gas companies. The return responses, however, show heterogeneous effects of structural shocks on upstream, midstream, and downstream oil and gas companies, suggesting that a well-diversified portfolio is obtainable.